Fuels and landscape flammability in an Australian alpine environment. (18th April 2016) - Fraser, Imogen P.; Williams, Richard J.; Murphy, Brett P.; Camac, James S.; Vesk, Peter A.
Abstract: Factors governing landscape‐scale flammability are poorly understood, yet critical to managing fire regimes. Studies of the extent and severity of the 2003 Australian alpine fires revealed marked differences in flammability between major alpine plant communities, with the occurrence and severity of fire greater in heathland compared to grassland. To understand this spatial variation in landscape flammability, we documented variation in two physical properties of fuel – load and bulk density – at the life‐form and plant community scale. We measured the load (mass per unit area) and bulk density (mass per unit volume) of fine fuels (<6 mm) at 56 sites across the Bogong High Plains, southeastern Australia. Fine fuel load was positively correlated with shrub cover, and fine fuel bulk density was negatively correlated with shrub cover. Furthermore, fine fuel load and bulk density were accurately predicted using simple measures of canopy height and shrub cover. We also conducted a burning experiment on individual shrubs and snowgrass ( Poa spp.) patches to assess comparative differences in flammability between these life‐forms. The burning experiment revealed that shrubs were more flammable than snowgrass as measured by a range of flammability variables. Consequently, our results indicate that treeless alpine landscapes of southeastern Australia are differentially flammable because of inherent life‐form differences in both fine fuel load and bulk density. If shrub cover increases in these alpine landscapes, as projected under climate change, then they are likely to become more flammable and may experience more frequent and/or severe fires.